Introduction, or, Is Blank Verse Black?. (3rd July 2022) - Stagg, Robert
ABSTRACT: This essay introduces the special issue 'Shakespeare and Versification', and then turns to think about the colouration and 'race-making' of blank verse. Could blank verse be black, and (how) can we think about questions of race in prosody?